Conservation Of Heritage Building Façade; The Case Study Of Traditional Tower Houses In Old Sana’a, Yemen - Abdulhameed, Noran Abduljabbar Mohammed (2024)
Old Sana'a's traditional tower houses, a UNESCO World Heritage Site, face ongoing threats from unregulated alterations and modern construction practices. These changes have compromised the buildings' authenticity and cultural significance, highlighting the need for a comprehensive approach to heritage conservation. This study investigates the relationship between authenticity and conservation interventions in the context of tower house façade preservation. Employing a qualitative methodology, this research delves into three case studies of tower houses that have undergone recent alterations, supplemented by interviews with heritage conservation experts. Fundamental authentic values embedded in the façades, such as material choices, design elements, and their relationship to the urban fabric, are identified and analysed. The study examines the extent to which conservation interventions have impacted these authentic values and evaluates their effectiveness in preserving the cultural heritage of Old Sana'a. Challenges such as the absence of clear guidelines, limited institutional capacity, and a lack of public awareness are underscored. Based on these findings, the research proposes a comprehensive conservation guideline that prioritises the preservation of authenticity. This guideline emphasises using traditional materials and techniques, carefully assessing proposed interventions, and robust community engagement. These recommendations aim to inform policy development, guide conservation practice, and raise public awareness, ultimately contributing to the long-term safeguarding of Old Sana'a's unique architectural heritage.